A eficácia dos princípios da razoabilidade e da proporcionalidade na perspectiva dos direitos fundamentais - Abad, Raphael Madeira (2007)
This thesis engaged in evaluating the way witch the reasonability and proportionality principles act in the legal system, serving as limits to the creation of rules in the plan of the statements or of the rules properly said, as the meaning in the intellect of the interpreter. Specifically, the performance of such principles that deal with fundamental rights was analysed when the creation of rules and statements. The reasonability and proportionality principles, although empirically used since classic ages, begun to deserve more attention by the right after the second half of XX century, especially the transgression of the fundamental rights occurred in its fist half. From now on it has been object of constant studies, on the part of the executive, the legislative and the judiciary . However, such studies do not reach the form with that the reasonability and proportionality principles act in the legal system. In such a way, it had the needs to define the rules concepts, analyzed its species, as well as the form which each one of them influences the creation of the others. Also it was necessary to know the reasonability and proportionality principles that, as they had not been expressed in the text of the Constitution, are interpreted form other constitutional statements. In such a way, the statements had been analyzed form the understanding of such principles. Knowing the performance of the reasonability and proportionality principles it was necessary to comprehend its application for the court of justice since XIX century, empathizing the jurisprudence of the United States, Germany and Brazil. Pursuant limites and possibilities of mentioned principles and how that such rules act in the creation of the others, it was necessary to inquire as they act in the system, serving as a limit of the expedition or reasonableness and disproportional statements, as well as the interpretation of any statement to violate such rights. Finally, it was necessary to demonstrate the performance of such technique as safeguards of the increasing roll of the fundamental rights.